2012
DOI: 10.1007/s00259-012-2270-1
|View full text |Cite
|
Sign up to set email alerts
|

Human biodistribution and dosimetry of 18F-JNJ42259152, a radioligand for phosphodiesterase 10A imaging

Abstract: In humans, (18)F-JNJ42259152 has an appropriate distribution, brain kinetics and safety. The estimated effective dose was within WHO class IIb with low interindividual variability. Therefore, the tracer is suitable for further kinetic evaluation in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…Time-integrated activity coefficients (formerly called residence times) were derived from the time-activity profiles. Individual organ doses and effective doses were determined using the OLINDA/EXM software (version 1.0; Vanderbilt University), with the same approach and curve-fitting procedures as applied previously (22).…”
Section: Discussionmentioning
confidence: 99%
“…Time-integrated activity coefficients (formerly called residence times) were derived from the time-activity profiles. Individual organ doses and effective doses were determined using the OLINDA/EXM software (version 1.0; Vanderbilt University), with the same approach and curve-fitting procedures as applied previously (22).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, a first-in-man biodistribution and dosimetry study showed that the tracer was safe and displayed promising kinetics for further quantitative evaluation of PDE10A activity in the nigrostriatal circuit (16).…”
Section: F-jnj-42259152 or 2-[[4-[1-(2-18 F-fluoroethyl)-4-(4-pyridimentioning
confidence: 99%
“…Potential ligands for PET imaging of PDE10A have been reported (19)(20)(21)(22)(23)(24). Papaverine, a widely used inhibitor of PDE10A activity, lacked suitable imaging characteristics when 11 C-labeled (22).…”
mentioning
confidence: 99%
“…18 F-JNJ41510417 was demonstrated to have good pharmacologic and anatomic specificity in rodent PET studies (23) but had a radiometabolite entering the brain. More recently, human studies with 18 F-JNJ42259152 were reported (20,25).…”
mentioning
confidence: 99%